2022
DOI: 10.3390/antiox11061091
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Assessment of Antioxidant Potential of Human Milk Treated by Holder Pasteurization or High Hydrostatic Pressure Processing: A Preliminary Study on Intestinal and Hepatic Markers in Adult Mice

Abstract: Preterm infants are highly susceptible to oxidative stress due to an imbalance between endogenous oxidant and antioxidant systems. In addition, these newborns are frequently fed with donor milk (DM) treated by Holder pasteurization (HoP) at 62.5 °C for 30 min, which is known to alter numerous heat-sensitive factors, including some antioxidants. High hydrostatic pressure (HHP) processing was recently proposed as an innovative method for the treatment of DM. The present study aimed to measure the redox balance o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…These mice also had an increased expression of some ileal tight junctions ( Ocln , Cdh1 ) and an augmented expression of the intestinal mucin Muc2 . Interestingly, in a recent study of our group, we showed that HHP-DM mice also displayed a stimulated antioxidant defense and a reduced expression of inflammatory markers in the ileum, compared with HoP-treated mice [ 19 ]. It is now well shown that the intestinal barrier function is strongly regulated by the redox homeostasis [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…These mice also had an increased expression of some ileal tight junctions ( Ocln , Cdh1 ) and an augmented expression of the intestinal mucin Muc2 . Interestingly, in a recent study of our group, we showed that HHP-DM mice also displayed a stimulated antioxidant defense and a reduced expression of inflammatory markers in the ileum, compared with HoP-treated mice [ 19 ]. It is now well shown that the intestinal barrier function is strongly regulated by the redox homeostasis [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many authors have shown significant decrease in bioactive factors in milk following HoP compared with HPP. Thus, immunoglobulins ( 42 , 43 , 50 ), lactoferrin ( 42 , 44 , 48 , 50 ), lysozyme ( 43 , 44 , 50 ), lipase activity ( 24 , 44 , 45 , 50 , 51 , 53 ) and many hormones ( 54 , 57 ) are largely affected by HoP.…”
Section: High Pressure Processing (Hpp)mentioning
confidence: 99%
“…Studies comparing mice fed HoP- and HPP-treated milk showed a loss of antioxidant defenses and an increase of inflammatory markers in animals fed HoP-treated milk ( 54 ).…”
Section: High Pressure Processing (Hpp)mentioning
confidence: 99%
“…While macronutrients are not impacted much through pasteurization, there is some evidence that they may reduce preterm infant fat absorption [8]. Additionally, heat treatment and cold storage impact many bioactive components of fresh human milk [9][10][11]; see Figure 1. Therefore, it is vital to recognize and consider the potential biological benefits of fresh parent's own milk on infant health and development.…”
Section: Introduction and Overview Of Nicu Practices And Implications...mentioning
confidence: 99%